2020
DOI: 10.1177/1120700020981573
|View full text |Cite
|
Sign up to set email alerts
|

Elective hip arthroplasty rates and related complications in people with diabetes mellitus

Abstract: Background and Aims: Diabetes mellitus (DM), poor glycaemic control and raised body mass index (BMI) have been associated with postoperative complications in arthroplasty, although the relative importance of these factors is unclear. We describe the prevalence of DM in elective hip arthroplasty in a UK centre, and evaluate the impact of these factors. Methods: We analysed retrospective data for DM patients undergoing arthroplasty over a 6-year period and compared with non-diabetic matched controls (1 DM patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Hyperglycemia directly contributes to the cartilage destruction observed in OA via oxidative stress, proinflammatory pathways, and acceleration of bone remodeling. This further reinforces the connections between these disorders [3] . The prevalence of DM in patients who undergo total hip arthroplasty (THA) and TKA might reach up to 52% [4] .…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Hyperglycemia directly contributes to the cartilage destruction observed in OA via oxidative stress, proinflammatory pathways, and acceleration of bone remodeling. This further reinforces the connections between these disorders [3] . The prevalence of DM in patients who undergo total hip arthroplasty (THA) and TKA might reach up to 52% [4] .…”
Section: Introductionsupporting
confidence: 78%
“…McVey et al [3] reported that Postoperative complications were equally likely in patients with DM (12.2%) and controls (12.9%) (p = 1.000). The impact of glycemic control on postoperative complications therefore remains unclear [3] . Our results aligned with the Aljuaid research as well.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of the non-diabetic patients, 8% had dysglycemia and 2% had undiagnosed diabetes. The prevalence of diagnosed diabetes varies substantially between countries and therefore also in studies on TJA, or between 6% and 12%, as does undiagnosed diabetes, or up to 41% (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DM is associated with an increased risk of undergoing orthopedic surgery, particularly THA. Furthermore, diabetes has been associated with postoperative complications in THA, including prosthetic joint infection, persistent pain, and increased hospital costs, particularly when diabetes is poorly controlled [ 8 ]. Previous investigations employing various methodologies have documented elevated complication rates and suboptimal outcomes, including increased implant loosening and dislocation, in patients with CKD undergoing total hip arthroplasty [ 9 ].…”
Section: Introductionmentioning
confidence: 99%